̈Realidad Económica del Financiamiento de los Comerciantes minoristas de la ciudad de Loja ̈ - Llivigañay López, Camila del Cisne (2025)
The present research work, titled "Economic Reality of Retailers' merchants Financing in the City of Loja," provides a contextual and exploratory analysis of the challenges associated with financing investments for retailers’ merchants in Loja. The general objective of this research work is to examine the financial reality that retailers’ merchants face daily. Additionally, specific objectives include identifying the primary sources of financing used by retailers’ merchants in Loja and uncovering the difficulties and barriers they encounter in securing financial support. This research work employs various research methods, including exploratory, descriptive, deductive, and analytical. The instruments used for data collection comprise direct observation and surveys administered to retailers in the city. The findings reveal multiple financial challenges, with a particularly concerning issue being the prevalence of informal credit, commonly referred to as "predatory loan" Notably, nearly 50% of merchants rely on this form of credit. This research work further identifies significant obstacles that retailers’ merchants face in accessing formal credit. To illustrate the financial impact, a comparative table analyzing interest rates between formal financial institutions and "predatory loan" loans was developed. Finally, this research work proposes a regulatory framework to mitigate the use of informal loans, targeting financial institutions, local government authorities, and the retail sector in Loja.